Intravenous fish oil containing lipid emulsion attenuates inflammatory cytokines and the development of bronchopulmonary dysplasia in very premature infants: A double-blind, randomized controlled trial. Issue 3 (June 2019) - Hsiao, Chien-Chou; Lin, Hung-Chih; Chang, Yu-Jun; Yang, Shih-Pan; Tsao, Lon-Yen; Lee, Cheng-Han; Chen, Hsiao-Neng; Chen, Jia-Yuh; Tsai, Yi-Giien
Summary: Background & aims: Preterm infants have lower levels of long-chain polyunsaturated fatty acids (LCPUFAs). Supplementing very premature infants with intravenous lipid emulsions that fish oil, which is rich in n-3 LC-PUFAs, may decrease bronchopulmonary dysplasia (BPD) by modulating inflammation and neonatal immune function. Methods: Sixty very low birth weight (VLBW) premature infants requiring ventilator support were randomized in a double-blind manner to 2 groups and received total parenteral nutrition with fish oil containing LE (intervention group, n = 30) or soybean oil containing LE (control group, n = 30) for 7 days. Blood samples and bronchoalveolar lavage fluid (BALF) were obtained for assay on day 1 and 7 days after LE. The primary outcome was to compare the levels of interleukin (IL)-1β and IL-6 in serum and BALF. Secondary outcomes were to compare mortality and co-morbidities. Results: The levels of IL-1β and IL-6 in serum and BALF were significantly lower in the intervention group at day 8 ( p  < 0.05). The incidence of BPD in the intervention group compared to the control group was 13.3% versus 36.7% ( p  = 0.04; odds ratio [OR], 0.36; 95% confidence interval [CI], 0.21–0.86). The duration of ventilator support and oxygen use was significantly less in the intervention group than in the control group ( p  < 0.05). The level of alanine aminotransferase was significantly lower in the intervention group on day 8 ( p  = 0.031). Conclusions: In very premature infants, early administration of fish oil containing LE significantly decreased IL-1β and IL-6 levels in serum and BALF and was associated with shorter duration of ventilator support and less bronchopulmonary dysplasia (BPD). Trial registration number: ISRCTN 11427103.